University Tutoring Service Assessment Scale (EVSTU): Construction and validation - Alegre Bravo, Alberto (2025)
Introduction: University tutoring is essential; it offers a comprehensive training approach for the student, in addition to improving retention and promotion at the university. Objective: validation of a rating scale for the university tutoring service among students of a private university in Lima, Peru. Method: A sample of 797 students (51.3% women, 48.7% men) aged between 16 and 43 years (M = 20.11; SD = 3.67) completed two questionnaires, UTSRS and NPS. The following analyses were carried out: descriptive of items, exploratory factorial, reliability, confirmatory factorial, correlation, and differences. Results: The 5 items obtained factor loadings greater than .32 with alpha and omega of .927 and .928 respectively. Discussion: It can be concluded that UTSRS is a valid measure regarding the assessment of the non-pedagogical tutoring service; It is important to consider that other studies should be carried out in similar contexts to verify the findings.